Weaving it together - Broukal, Milada (Heinle & Heinle, 2004)
A favorite over a decade, WEAVING IT TOGETHER connects high-interest readings with clear writing activities to help students be more confident in their ability to understand and express ideas in English. Each level of WEAVING IT TOGETHER, 2/e contains eight thematically organized units, each of which includes two interrelated chapters. Robust activities, structure lessons, and plenty of writing practice help students develop their ideas clearly and with confidence.